Eksistensi Pemaknaan Santet pada Pembaharuan Hukum Pidana: Telaah Rancangan Kitab Undang-Undang Hukum Pidana Indonesia - Anwar, Reski (Fakultas Syariah dan Ekonomi Islam, IAIN Syaikh Abdurrahman Siddik, Bangka Belitung, 2021)
This paper discusses about witchcraft which is one of the controversial delict in draft criminal law september 2019 (RKUHP) in Indonesia. This is because most of the general public assumes that witchcraft is believed to be an act that can harm people, suffer and or even kill people. However, in accordance with the principle of legality and the difficulty of proof, witchcraft deeds so far can not be entered into the realm of justice so that it is not uncommon for people accused of witchcraft to lose their lives without going through legal process. Therefore, in this study by analyzing the witchcraft delict in the construction of RKUHP this study uses normative legal research methods whose data are obtained through literature studies. The results obtained revealed that witchcraft is a criminal act that must be constructed into the category of delik formil whose proof does not necessarily lead to the existence or absence of a supernatural force it self owned by the perpetrator or individual. However, what can be used as a delik is a criminal act committed that is a person who deliberately announces himself to have supernatural powers as article 252 paragraph 1 RKUHP.